Kelompok Psikoedukatif Daring untuk Kesehatan Mental Siswa: Strategi dan Tantangan dalam Layanan Bimbingan dan Konseling di Sekolah - Carissa Candyanta Kusuma Wardani; Muslikah; Awalya (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2026)
Students' mental health has become a major concern in educational settings because it is closely associated with learning abilities, social relationships, and personality development. Issues such as academic stress, anxiety, social pressure, and poor emotional regulation indicate the need for effective and easily accessible psychological support services. This study aims to examine the strategies, challenges, and impacts of online psychoeducational groups as an innovative guidance and counseling service to support students' mental health through a scoping review approach. The research focuses on the implementation of service strategies, barriers to implementation, and the contribution of online psychoeducational groups to the development of students' mental health based on findings from previous studies. This review analyzed eight articles retrieved from the Google Scholar, ScienceDirect, and JMIR databases using publication year (2017–2026), topic relevance, and data availability as the selection criteria. The findings indicate that online psychoeducational groups are implemented through video conferencing, structured learning materials, group discussions, self-reflection, and interactive activities that enhance students' mental health literacy, emotional regulation, coping skills, and self-confidence. The findings also emphasize the importance of ensuring the sustainability of these services.